An introduction to social media marketing - Charlesworth, Alan 1956- (Routledge, Taylor & Francis Group, 2015)
"Although the Internet has had a massive impact on both society and business, it is the public's adoption of social media which provides its most significant legacy to date, and arguably the technology with the greatest potential for creative marketers. Nevertheless, its newness is also a challenge, particularly to those of us that aren't "digital natives". This is the first textbook for students that offers a step by step guide to social media marketing. Mirroring its sister text Digital Marketing: a Practical Approach, this book is grounded in solid academic underpinnings, but has a lighter, hands-on approach that is perfect for shorter courses and additional reading. Each section includes bespoke case studies developed to tests the learners' understanding of how the various concepts, models and examples are best applied in real-world scenarios. Moreover, it's supported by the author's excellent website, with a continually updated blog, further cases, and examples of good and bad practice from current events. Topics covered in this book include: BlogsMobile MarketingOnline communities social networks Strategic SMMAnd much more. Social Media Marketing is the first of its kind and ideal reading for students who want to work in a digital marketing environment, as well as the traditional marketer who wants to get to grips with this vibrant, and potentially lucrative tool"--Provided by publisher.